Tumor necrosis factor receptor p55 mediates deletion of peripheral cytotoxic T lymphocytes in vivo. - Speiser, D; Sebzda, E; Ohteki, T; Bachmann, M; Pfeffer, K; Mak, T; Ohashi, P (1996)
Cellular death of activated lymphocytes down-regulates immune responses and is involved in maintaining self tolerance. Signals associated with ligation of the membrane molecule Fas lead to lymphocyte apoptosis, but additional, Fas-independent mechanisms have been postulated. Here, we show a marked expansion and prolonged persistence of functional activated cytotoxic T cells in mice lacking the tumor necrosis factor (TNF) receptor p55. In the absence of this receptor, peripheral lymphocyte apoptosis was significantly reduced in vivo. The prolonged thymocyte survival was associated with functional anergy, since the T cells no longer proliferated in vitro when stimulated with peptide antigen. However, specific cytotoxic effector function was easily detected in vitro. We conclude that the TNF receptor p55 is involved in peripheral T cell deletion in vivo.